2019
DOI: 10.1002/mnfr.201900644
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of an Iron Supplement on Lycopene Metabolism and Absorption During Digestion in Healthy Humans

Abstract: Scope To investigate the formation and absorption of lycopene (LYC) metabolites in the human upper gastrointestinal lumen, in the absence and presence of iron. Methods Healthy males (n = 7) consumed test meals that deliver ≈22 mg LYC + ≈0.3 mg apo‐lycopenals from oleoresin without (‐FeSO4) and with ferrous sulfate (160 mg, +FeSO4). Subjects were intubated with a naso‐gastric/naso‐duodenal tube. Digesta, blood plasma, and the triglyceride‐rich lipoprotein (TRL) fractions of plasma were analyzed using LC–MS/MS, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 53 publications
1
15
0
Order By: Relevance
“…Lycopene is among the most effective carotenoid free-radical scavengers, because the free radical compound formed with lycopene is more stable than that formed with other compounds in this group, which indicates that it can reduce, through electron transfer, also other carotenoids (25) . In vitro studies conducted by Wawrzyniak (49) found lycopene to be stable in acid and neutral gastric content, which was confirmed by the work of other authors (50) and also in the upper intestine (51) . The addition of lycopene and sodium nitrite to stomach content at the same time caused a significant decrease in the content of lycopene, and significantly lowered the concentration of sodium nitrite (49) ; lycopene decrease depended on the amount of nitrite added.…”
Section: Antioxidant Activitiessupporting
confidence: 64%
“…Lycopene is among the most effective carotenoid free-radical scavengers, because the free radical compound formed with lycopene is more stable than that formed with other compounds in this group, which indicates that it can reduce, through electron transfer, also other carotenoids (25) . In vitro studies conducted by Wawrzyniak (49) found lycopene to be stable in acid and neutral gastric content, which was confirmed by the work of other authors (50) and also in the upper intestine (51) . The addition of lycopene and sodium nitrite to stomach content at the same time caused a significant decrease in the content of lycopene, and significantly lowered the concentration of sodium nitrite (49) ; lycopene decrease depended on the amount of nitrite added.…”
Section: Antioxidant Activitiessupporting
confidence: 64%
“…Moreover, people observed that after drinking a tomato shake, the blood levels of lycopene were significantly lower in participants who had also taken an iron supplement [[ 88 ]]. That only supports the above-mentioned facts that excess of iron ions results in higher ROS production.…”
Section: Therapeutic Properties Of Lycopenementioning
confidence: 99%
“…Lipids were extracted from cells using a modified Bligh–Dyer method, as described previously . The extracts obtained from four wells were pooled to optimize the metabolite concentration for NMR analysis.…”
Section: Methods and Experimental Sectionmentioning
confidence: 99%
“…Lipids were extracted from cells using a modified Bligh− Dyer method, as described previously. 42 The extracts obtained from four wells were pooled to optimize the metabolite concentration for NMR analysis. Extracts were also analyzed using ultrahigh-performance liquid chromatography-high-resolution mass spectrometry (UHPLC−HRMS) using a 1290 UHPLC system interfaced with a Q-Tof 6545 (Agilent, Inc.) with an electrospray probe operated in a positive ion mode.…”
Section: Sample Preparationmentioning
confidence: 99%